2020
DOI: 10.1007/s10549-020-05836-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate mediators of chemoresponse in breast cancer through therapy-driven selection of somatic variants

Abstract: Purpose More than a third of primary breast cancer patients are treated with cytotoxic chemotherapy, typically without guidance from predictive markers. Increased use of neoadjuvant chemotherapy provides opportunities for identification of molecules associated with treatment response, by comparing matched tumour samples before and after therapy. Our hypothesis was that somatic variants of increased prevalence after therapy promote resistance, while variants with reduced prevalence cause sensitivity. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Genetic markers have been explored as a predictor of the antitumor response or chemoresistance, and the use of next-generation sequencing provided a new perspective for marker identification. Several markers were previously associated with BC drug sensitivity or resistance [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. Gong et al [ 62 ] evaluated a cohort of 421 patients with luminal A BC from two different stages using genotyping from peripheral blood.…”
Section: Markers Associated With the Chemotherapy Responsementioning
confidence: 99%
“…Genetic markers have been explored as a predictor of the antitumor response or chemoresistance, and the use of next-generation sequencing provided a new perspective for marker identification. Several markers were previously associated with BC drug sensitivity or resistance [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. Gong et al [ 62 ] evaluated a cohort of 421 patients with luminal A BC from two different stages using genotyping from peripheral blood.…”
Section: Markers Associated With the Chemotherapy Responsementioning
confidence: 99%
“…From a research perspective, neoadjuvant chemotherapy provides the further advantage that matched tumour tissue from pre- and post-therapy can be available, allowing for the comparative identification of the therapy-associated changes within the cancer cells that may be associated with relative chemotherapy resistance. This strategy has been used successfully by our team and others, to identify chemoresponse-associated somatic mutations [ 6 , 7 , 8 ], and changes in protein [ 9 , 10 ] or mRNA expression [ 8 , 11 ]. MicroRNAs have received less attention in this context, with only a total of five previous studies following this design [ 12 , 13 , 14 , 15 , 16 ], leading to identification of only one microRNA, miR-18a, as a potential mediator of chemoresistance [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In line with previously published articles, CACNA1C was up-regulated in brain tumors, leukemia, breast cancer and other tumors [ 14 ]. Besides, variants of CACNA1C were associated with bladder cancer, endometrial cancer and breast cancer risk [ 15 , 32 , 33 ]. All of these indicated that CACNA1C could also be a prognostic predictor for patients with OC.…”
Section: Discussionmentioning
confidence: 99%